Letter: the combination of histologic remission and Mayo endoscopic score 1 as a suitable therapeutic target in ulcerative colitis—authors' reply. Issue 8 (21st March 2021) - Jangi, Sushrut; Yoon, Hyuk; Dulai, Parambir; Valasek, Mark; Boland, Brigid; Jairath, Vipul; Feagan, Brian; Sandborn, William; Singh, Siddharth
Abstract : LINKED CONTENT This article is linked to Jangi et al and Maeda et al papers. To view these articles, visit https://doi.org/10.1111/apt.16026 and https://doi.org/10.1111/apt.16302